Recent Developments in the Facile Bio-Synthesis of Gold Nanoparticles (AuNPs) and Their Biomedical Applications - Lee KX (Dove Medical Press, 2020)
Kar Xin Lee, 1 Kamyar Shameli, 1 Yen Pin Yew, 1 Sin-Yeang Teow, 2 Hossein Jahangirian, 3 Roshanak Rafiee-Moghaddam, 3 Thomas J Webster 3 1Department of Environmental Engineering and Green Technology, Malaysia–Japan International Institute of Technology, Universiti Teknologi Malaysia, Kuala Lumpur 54100, Malaysia; 2Department of Medical Sciences, School of Healthcare and Medical Sciences (SHMS), Sunway University, Jalan Universiti, Bandar Sunway 47500, Selangor Darul Ehsan, Malaysia; 3Department of Chemical Engineering, 313 Snell Engineering Center, Northeastern University, Boston, MA, USACorrespondence: Kamyar Shameli; Hossein Jahangirian Tel +6 017 344-3492; +1 617 860-8429Email kamyarshameli@gmail.com; kamran.jahangirian@gmail.comAbstract: Gold nanoparticles (AuNPs) are extensively studied nanoparticles (NPs) and are known to have profound applications in medicine. There are various methods to synthesize AuNPs which are generally categorized into two main types: chemical and physical synthesis. Continuous efforts have been devoted to search for other more environmental-friendly and economical large-scale methods, such as environmentally friendly biological methods known as green synthesis. Green synthesis is especially important to minimize the harmful chemical and toxic by-products during the conventional synthesis of AuNPs. Green materials such as plants, fungi, microorganisms, enzymes and biopolymers are currently used to synthesize various NPs. Biosynthesized AuNPs are generally safer for use in biomedical applications since they come from natural materials themselves. Multiple surface functionalities of AuNPs allow them to be more robust and flexible when combined with different biological assemblies or modifications for enhanced applications. This review focuses on recent developments of green synthesized AuNPs and discusses their numerous biomedical applications. Sources of green materials with successful examples and other key parameters that determine the functionalities of AuNPs are also discussed in this review.Keywords: biosynthesis, green materials, gold nanoparticles, AuNPs, biomedical applications